Chromosome study in spontaneous abortion and its clinical application - Quiroga de Michelena, María Isabel (2015)
OBJECTIVES: To describe the frequency of chromosome anomalies in spontaneous abortions, the influence of maternal and gestational age, and the application of this knowledge in obstetrical practice, and in future pregnancies management. DESIGN: Descriptive transversal study. SETTING: Genetics Medical Institute, Lima, Peru. MATERIALS: Spontaneous abortions samples recieved for study between 1995 and 2007. INTERVENTIONS: Data of 1088 spontaneous abortions samples were obtained and karyotype, maternal age and gestational age were analyzed. MAIN OUTCOME MEASURES: Karyotype normality or abnormality, maternal age. RESULTS: Karyotype was normal in 332 (30,5%) of the 1088 samples and abnormal in 756 (69,5%). Among chromosomal anomalies, aneuploidy showed a frequency of 60,3%, polyploidy, 16,4%, and X monosomy, 9,5%. Prevalence of aneuploidy rose with maternal age. CONCLUSIONS: Cytogenetic study of spontaneous abortion is useful to determine gestational loss cause and diagnosis, plan future pregnancies and inform the couple on prognosis.